( 100 – 1) x (100 -2 ) x . . . x ( 100 -99 ) x ( 100 – 100 ) : (500xx + 200) =………………………

Question

( 100 – 1) x (100 -2 ) x . . . x ( 100 -99 ) x ( 100 – 100 ) : (500xx + 200) =………………………

in progress 0
Eliza 2 ngày 2021-12-07T12:34:16+00:00 2 Answers 4 views 0

Answers ( )

    0
    2021-12-07T12:35:33+00:00

    Đáp án:

    ( 100 – 1) x (100 -2 ) x . . . x ( 100 -99 ) x ( 100 – 100 ) : (500xx + 200)

    = ( 100 – 1) x (100 -2 ) x . . . x ( 100 -99 ) x 0 : (500xx + 200)

    = 0 : (500xx + 200)

    = 0

    Giải thích các bước giải:

     

    0
    2021-12-07T12:36:08+00:00

    Đáp án:

    `( 100 – 1) × (100 -2 ) × … × ( 100 -99 ) × ( 100 – 100 ) : (500×x + 200)`

    `= ( 100 – 1) × (100 -2 ) × … × ( 100 -99 ) × 0 : (500×x + 200)`

    `= 0:(500×x + 200)`

    `= 0`

     

Leave an answer

Browse

35:5x4+1-9:3 = ? ( )